A study on expressway merging and diverging traffic operation / Nurul Qastalani Radzuan - Radzuan, Nurul Qastalani (2015)
Merging lane is a path for drivers to accelerate their vehicle at a desired speed from the ramp terminal prior into entering the highway main stream. Conversely, diverging lanes allow the drivers to slow down their vehicle enabling them to enter the ramp terminal conveniently. The length of the speed-change lane should be in optimum design to ensure that the drivers are allowed to make appropriate lane changes. AASHTO (2004) provides a minimum merging lane length for entrance terminals and also a minimum diverging lane length by considering the design speed of ramp terminal and design speed of highway main stream without considering flow rates of influenced area. This research proposed a novel merging and diverging model using statistical platform called Minitab to predict merging and diverging lane lengths, respectively based on macroscopic parameters for Malaysia road traffic conditions. A video recorded traffic empirical data was collected and the post processing analysis was conducted by means of Semi-Automatic Video Analyser (SAVA). The validation of the proposed model is performed by comparing the predicted length data of the model with the empirical length data using paired t-test. The effect of merging and diverging lane lengths were further analysed by using the collected empirical speed data of merging and diverging speed on the ramp and the effective length used for the traffic operation on ramps. The research observed macroscopic and microscopic parameters have significant findings towards the traffic operation